An App for parking with indoor navigation facility - Atiqur Rahman; Bosco, Musabe Jean (Penerbit Universiti Kebangsaan Malaysia, 2023)
There are numerous parking supervision and random booking procedures that regulate parking operations. Travel time to the parking slot and walking time inside the terminus can still be dropped if the parker can book a precise parking spot instead of an arbitrary one. This is achieved by our proposal, called sPark which is an app-based parking method that includes indoor navigation facility i.e., an app for parking with indoor navigation facility. sPark’s sharing system will rapidly book the optimal parking slots for parkers and advise them on the best feasible entrances for practice. Also, parkers will find the briefest path to their target using our proposed app’s navigation technique, saving them a lot of time roaming to the building. Different parking methods like sPark (our proposed), non-directed and directed methods (existing) are designed and assessed. The designed and assessed simulation outcomes of sPark indicate an important decrease in the overall driving time by 30% to 60% as compared to the non-directed method which is an existing method. Additionally, the resource sharing module in our scheme i.e., an app for parking with indoor navigation facility called sPark has revealed a 9.99% decrease in driving time in comparison to directed methods (existing) that feature interior cruising and direction only.